Analysis of the Management Impact of Village Funds on the Village Development (The Study Case of the Sermong Villages of West Sumbawa). - Elya Resta Desthasya; Hailuddin, Hailuddin; Baiq Saripta Wijimulawiani (Experimental Student Experiences, 2024)
The aim of the study is to analyze the management of village funds to improve the development of villages and to analyze the management of village funds in the impact on village development in the village of sermong, sumbawa west district. The study employed qualitative methods for conducting interviews with respondents, namely by interviewing the people of the Sermong village as the chief informer, was strengthened with the government of the Sermong village as a key informant. For more information, interviews are made on village heads, neighborhood committees and mosque youth as additional informers. The result of this study suggests that the efforts of rural governments to boost development include physical and non-physical infrastructure. The management of village funds has a positive impact on development in the Sermong village in both physical and nonphysical development. However, there is a challenge in the process of management, which is the availability of human resources, where human resources in the village of Sermong are still below average.